2019
DOI: 10.1111/jce.14176
|View full text |Cite
|
Sign up to set email alerts
|

Physical, cognitive, and psychosocial conditions in relation to anticoagulation satisfaction among elderly adults with atrial fibrillation: The SAGE‐AF study

Abstract: Background Successful anticoagulation is critical for stroke prevention in adults with atrial fibrillation (AF). Anticoagulation satisfaction is a key indicator of treatment success. While physical, cognitive, and psychosocial limitations are common in elderly AF patients, their associations with anticoagulation satisfaction are unknown. Objective Examine whether anticoagulation satisfaction differs among AF patients with and without physical, cognitive, and psychosocial conditions. Methods The study comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
(62 reference statements)
0
23
0
Order By: Relevance
“…Using data from the ongoing SAGE (Systematic Assessment of Geriatric Elements)-AF study, (17,18) we examined the extent to which older men and women with nonvalvular AF (NVAF) were engaged in the decision-making process to take OAC for stroke prevention. We hypothesized that patient engagement in SDM would be modest, with a need for better patient engagement, and that advancing age would be inversely related with being part of this process.…”
Section: Factors Associated With Patient Engagement In Shared Decision-making For Stroke Prevention Among Older Adults With Atrial Fibrilmentioning
confidence: 99%
See 1 more Smart Citation
“…Using data from the ongoing SAGE (Systematic Assessment of Geriatric Elements)-AF study, (17,18) we examined the extent to which older men and women with nonvalvular AF (NVAF) were engaged in the decision-making process to take OAC for stroke prevention. We hypothesized that patient engagement in SDM would be modest, with a need for better patient engagement, and that advancing age would be inversely related with being part of this process.…”
Section: Factors Associated With Patient Engagement In Shared Decision-making For Stroke Prevention Among Older Adults With Atrial Fibrilmentioning
confidence: 99%
“…As part of an ongoing prospective study, adults aged 65 years and older with AF were recruited from five medical centers in Massachusetts and Georgia between 2015 and 2018. (17,18) The eligibility criteria for enrollment in SAGE-AF included: a) having a CHA2DS2-VASc (congestive heart, failure, hypertension, age [>75 years], diabetes, stroke, vascular disease, age [65 to 74 years], female gender) (19) score ≥2, and b) having a scheduled ambulatory care visit at any of the study clinic sites. Participants were not included in this study if they were unable to provide written informed consent, had a documented contraindication to OAC therapy (i.e., history of intracranial hemorrhage, mechanical heart valve, end-stage renal disease) or were on OAC for different indications other than AF, had a scheduled procedural intervention that was associated with an increased risk for bleeding, were non-English speakers, or were prisoners.…”
Section: Study Populationmentioning
confidence: 99%
“…[3][4][5] However nonadherence with OAC therapy is common and has been significantly associated with poor outcomes such as ischemic stroke, systemic embolism, higher healthcare costs, and higher mortality rate compared to adherent patients. 6,7 Satisfaction has been associated with various outcomes, including adherence to therapy in a range of diseases. 8,9 Studies on patients with AF on OAC therapy have also identified treatment satisfaction as an important psychosocial determinant of adherence to therapy, with lower satisfaction with OAC treatment being a significant predictor of stroke/systemic embolism, mediated by OAC nonadherence and non-persistence.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Studies on patients with AF on OAC therapy have also identified treatment satisfaction as an important psychosocial determinant of adherence to therapy, with lower satisfaction with OAC treatment being a significant predictor of stroke/systemic embolism, mediated by OAC nonadherence and non-persistence. 7,[10][11][12][13] In patients with AF on direct oral anticoagulants (DOACs), low satisfaction with benefits of therapy is independently associated with a three-fold increase in the incidence of stroke. 11 Reasons for lack of satisfaction include factors related to the patient and to the OAC itself such as the need for routine blood work monitoring, treatment-associated bleeding, drug and dietary interactions, dosing schedule, and cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation